1990
DOI: 10.1161/01.str.21.4.560
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal echocardiography in the detection of intracardiac embolic sources in patients with transient ischemic attacks.

Abstract: Using both precordial and transesophageal echocardiography, we studied 72 consecutive patients with a recent unequivocal transient ischemic attack or nondisabling stroke to determine the relative value of the two techniques for detecting potential intracardiac sources of cerebral emboli. Group 1 (n=53) patients had no clinical cardiac abnormality, and group 2 (n=19) patients had abnormal cardiac findings upon clinical examination. In group 1, precordial echocardiography detected an abnormality in only one pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(47 citation statements)
references
References 24 publications
2
43
0
2
Order By: Relevance
“…However, TEE enables us to repeatedly investigate the thoracic aorta in a noninvasive manner. In fact, several studies focusing on the thoracic aorta as a possible embolic source have been published recently (1)(2)(3)(4)(5)(6)(7)(8). Amarencoet al (1) defined aortic ulceration as a disruption of the intimal surface that was visible on macroscopicexamination.…”
Section: Discussionmentioning
confidence: 99%
“…However, TEE enables us to repeatedly investigate the thoracic aorta in a noninvasive manner. In fact, several studies focusing on the thoracic aorta as a possible embolic source have been published recently (1)(2)(3)(4)(5)(6)(7)(8). Amarencoet al (1) defined aortic ulceration as a disruption of the intimal surface that was visible on macroscopicexamination.…”
Section: Discussionmentioning
confidence: 99%
“…4 A significant number of these abnormalities can be readily identified by transthoracic or transesophageal echocardiograpy. 5 However, the specific cause of cerebral infarction is often elusive. The National Institute of Neurological Disorders and Stroke (NINDS) Stroke Data Bank, a large prospective study of more than 1800 patients, showed that 40% of cases of cerebral infarction were "of undetermined cause."…”
mentioning
confidence: 99%
“…Most cardiologists believe that TTE is insufficient in the evaluation of LAA morphology, size, and function for establishing its embolic potential (Mügge et al 1990;Heppell et al 1997), mainly because previous studies using fundamental imaging technology have demonstrated unsatisfactory sensitivity to detect thrombus (Shrestha et al 1981;Otto 2002). On the other hand, TEE has been considered the gold standard for LAA assessment (Pop et al 1990;Lee et al 1991;Pearson et al 1991;Mügge et al 1994;Santiago et al 1994;Ito et al 1996), as it allows accurate evaluation of this structure in virtually all patients. However, this technique is semiinvasive, uncomfortable, costly, and carries its own risks (Daniel et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is desirable to obtain at least some information regarding LAA function by transthoracic echocardiography (TTE) in patients having cardioembolic stroke. In this context, previous reports demonstrated that TTE has limited accuracy to detect abnormalities related to LAA morphology and function (Pop 1990;Cujec et al 1991;Lee et al 1991;Pearson et al 1991). On the other hand, several recent studies have used the velocities of LAA contraction as the possible surrogates of global left atrial contractile function (Ito et al 1997;Daoud et al 1999;Sparks et al 1999).…”
Section: Transthoracic Echocardiographic Predictors Of the Left Atriamentioning
confidence: 99%